Supervision of Education and Implementation of Santri Character Formation in Pesantren - Mu'alina, Nur; Khaudli, Muhammad Imam; Aimah, Siti (EDUTEC : Journal of Education And Technology, 2024)
The character of santri is one of the objectives of implementing educational supervision in Islamic boarding school education units. The aim of this research is to analyze and interpret the implementation of educational supervision in forming the character of santri in the educational unit at the Darussalam Islamic Boarding School Blokagung Banyuwangi, East Java, Indonesia. This research approach method uses a qualitative case study with key informants, the Head of education and teaching and members of the quality assurance unit using the Miles and Huberman interactive analysis model. The research results show that the character of santri who require continuous coaching is related to increased behavior, responsibility, honesty, discipline, thriftiness, caring and independence. Implementing supervision of santri character education as an evaluation of the implementation of institutional quality assurance by continuing to improve coordination, communication and collaboration in handling student problems. Integrated development that is controlled through standard operating procedures as an evaluation of the results of monitoring the character of santri and improving governance can be an effort to improve the quality of education.